Urban(izing) University strategic planning: An analysis of London and New York City - Addie, Jean-Paul D. (Urban Affairs Review)
While there is a growing recognition of the mutually beneficial relationships universities and cities can forge around local and regional development, urban and academic leaders have often struggled to harness the diverse capacities of universities as producers and analysts of urban space. This article addresses this challenge by examining the institutional and spatial strategies being prioritized by universities in the context of global urbanization. It details a Lefebvrian-influenced conceptual and methodological approach to evaluate the multifaceted, multiscalar urban(izing) functions of (3z(Buniversities in urban society.(3y (BComparatively assessing the organizational structures, spatial orientations, and ways of operating being pursued by universities in London and New York City reveals the scope$1 (Band variation$1 (Bof university urbanism within and across global urban higher education systems. The empirical analysis points toward the need for adaptive approaches through which urban actors can leverage universities in the analysis and governance of urban processes. Conclusions are drawn for public policy and university outreach. - Reproduced.s
Keywords: Higher education